Decoupled dual‐channel loosely coupled transformer with hybrid nanocrystalline and ferrite core for current sharing of modular wireless power transfer system - Yu Han; Zihan Tian; Liangchen Li; Song Li; Fuyao Yang; Jiaqi Chen; Rong Fan; Haisen Zhao (IET Power Electronics)
Abstract Cross‐coupling and current sharing are the main problems faced by modular wireless power transfer (WPT) systems for electric vehicle (EV) applications. In this study, a decoupled dual‐channel wireless power transfer loosely coupled transformer (LCT) with a hybrid core composed of nanocrystalline and ferrite is proposed for modular WPT systems, as well as WPT systems with specific hybrid topology or detuned compensation. Firstly, the requirements of the LCT for modular parallel dual‐channel WPT system and detuned compensation are discussed. For these requirements, the structure and corresponding optimization design method of the decoupled dual‐channel LCT with a hybrid core is then proposed, and an LCT is designed with this method for the case study. Furthermore, the LCT is analysed by the finite element method (FEM). It is revealed that the mutual inductances of the proposed LCT between transmitting and receiving coils can be symmetrical under misalignment in multiple directions, while the cross‐coupling is eliminated. Finally, the designed LCT is manufactured and verified in a modular parallel dual‐channel WPT system. The experimental results show that the current and power sharing is realized under misalignment in multiple directions.